Dynamic light scattering microrheology for soft and living materials. Issue 7 (11th January 2021) - Cai, Pamela C.; Krajina, Brad A.; Kratochvil, Michael J.; Zou, Lei; Zhu, Audrey; Burgener, Elizabeth B.; Bollyky, Paul L.; Milla, Carlos E.; Webber, Matthew J.; Spakowitz, Andrew J.; Heilshorn, Sarah C.
Abstract : We present a method for using dynamic light scattering in the single-scattering limit to measure the viscoelastic moduli of soft materials. Abstract : We present a method for using dynamic light scattering in the single-scattering limit to measure the viscoelastic moduli of soft materials. This microrheology technique only requires a small sample volume of 12 μL to measure up to six decades in time of rheological behavior. We demonstrate the use of dynamic light scattering microrheology (DLSμR) on a variety of soft materials, including dilute polymer solutions, covalently-crosslinked polymer gels, and active, biological fluids. In this work, we detail the procedure for applying the technique to new materials and discuss the critical considerations for implementing the technique, including a custom analysis script for analyzing data output. We focus on the advantages of applying DLSμR to biologically relevant materials: breast cancer cells encapsulated in a collagen gel and cystic fibrosis sputum. DLSμR is an easy, efficient, and economical rheological technique that can guide the design of new polymeric materials and facilitate the understanding of the underlying physics governing behavior of naturally derived materials.